Cardiac doses of accelerated partial breast irradiation with perioperative multicatheter interstitial brachytherapy - Novotná, Veronika; Sirák, Igor; Pohanková, Denisa; Jandík, Pavel; Kašaová, Linda; Grepl, Jakub; Paluska, Petr; Motyčka, Petr; Asqar, Ahmed; Kretzler, Lucie; Petera, Jiří (Strahlentherapie und Onkologie, 2021)
PURPOSE: To quantify mean heart dose (MHD) and doses to the left anterior descending artery (LAD) and left ventricle (LV) in a retrospective series of patients who underwent perioperative accelerated partial breast irradiation with multicatheter interstitial brachytherapy (MIB-APBI). METHODS: Sixty-eight patients with low-risk left breast cancer were treated with MIB-APBI at our institution between 2012 and 2017. Interstitial tubes were inserted during the tumorectomy and sentinel node biopsy and APBI was started 6 days later. The prescribed dose was 34 Gy in 10 fractions (twice a day) to the clinical target volume (CTV). The heart, LAD, and LV were contoured and the distance between each structure and the CTV was measured. The MHD, mean and maximum LAD doses (LAD mean/max), and mean LV doses (LV mean) were calculated and corrected to biologically equivalent doses in 2‑Gy fractionation (EQD2). We also evaluated the impact of the distance between the cardiac structures and the CTV and of the volume receiving the prescribed dose (V100) and high-dose volume (V150) on heart dosimetry. RESULTS: Mean EQD2 for MHD, LAD mean/max, and mean LV were 0.9 ± 0.4 Gy (range 0.3-2.2), 1.6 ± 1.1 Gy (range, 0.4-5.6), 2.6 ± 1.9 Gy (range, 0.7-9.2), and 1.3 ± 0.6 Gy (range, 0.5-3.4), respectively. MHD, LAD mean/max, and LV mean significantly correlated with the distance between the CTV and these structures, but all doses were below the recommended limits (German Society of Radiation Oncology; DEGRO). The MHD and LV mean were significantly dependent on V100. CONCLUSION: Perioperative MIB-APBI resulted in low cardiac doses in our study. This finding provides further support for the value of this technique in well-selected patients with early-stage left breast cancer.
Keywords: Left breast irradiation; Humans; lidé středního věku; Female; Radiotherapy Dosage; Breast; celková dávka radioterapie; Cardiac doses; lidé; Radiotherapy; APBI; Breast Neoplasms; ženské pohlaví; Middle Aged; Retrospective Studies; Heart; nádory prsu; retrospektivní studie; prsy; Cardiotoxicity; brachyterapie; srdce; Brachytherapy